Developing English Workbook Based On Task Based Approach For First Grade Students Of Smp Negeri Satu Atap SumberejoDeveloping English Workbook Based on Task Based Approach for First Grade Students of SMP Negeri Satu Atap Sumberejo - Damayanti Erviana (Language-Edu, 2019)
This study aims to develop the supplementary English reading materials based on task based approach for the seventh grade of  SMP Negeri Satu Atap Sumberejo. This study was conducted in order to solve the problem faced by the first grade of SMP Negerei Satu Atap Sumberejo in reading interest. The problem is about language that used in their workbook is not appropriate with their level, their workbook lack of explanation and task. Because of that the researcher wants to develop students English workbook based on students need.The result of this study is Workbook based on the students’ need. This workbook for first grade of SMP Negeri Satu Atap Sumberejo. The workbook consists of texts of the standardized materials for seventh grade in the syllabus of Curriculum 2013. With the picture to explain the materials and attractive exercise of this workbook, the student will be motivated to learn English language in the class and it supports the student in activating themselves into integrated activities in the class. So the students in seventh grade junior high school have more experiences in practicing English.